BS11. Somatosensory evoked potentials of the median nerve as a potential predictive marker of the clinical outcome in severe hemorrhagic stroke patients. (May 2018) - Gabelic, Tereza; Skorić, Magdalena Krbot; Blazevic, Nikola; Dapic, Biljana; Matijevic, Vesna; Supe, Svjetlana; Alvir, Domagoj; Bazina, Antonela; Ljevak, Josip; Starcevic, Katarina; Jovanovic, Ivan; Habek, Mario; et al.
Abstract : Introduction: Previous studies indicated an association between abnormalities of evoked potentials and clinical course in ischemic stroke patients. Our goal was to assess the usefulness of the evoked potentials in the prediction of the clinical outcome in severe hemorrhagic stroke patients. Methods: In 40 patients (21 men, mean age 63.50 ± 13.58) with hemorrhagic stroke (30 intracerebral and 10 subarachnoid hemorrhage), within the 48 h after admission to neurointensive care unit (NICU), brainstem auditory evoked potentials (BAEP) and somatosensory evoked potentials (mSSEP) of the median nerve were performed according to previously published guidelines. Among clinical parameters, the Glasgow Coma Score (GCS) and the Full Outline of Unresponsiveness (FOUR) were assessed on the admission date and on the day of discharge. Modified Rankin scale (mRS) was assessed on the day of discharge. Results: There was a statistically significant negative correlation between FOUR score at the day of admission and right BAEP latency of V wave (r s = −0.315, p = 0.048). There was also the significant negative correlation between left BAER III-V wave interlatency and FOUR score on the day of discharge (r s = −0.340, p = 0.032) and significant positive correlation of left BAER III-V wave interlatency and mRS on the day of discharge (r s = 0.316, p = 0.047). There were no significant correlations of clinical outcomes with BAEP amplitude. Regarding mSSEP results, significant negative correlation was found between right and left P14-N20 interlatenties and FOUR score on the admission date (r s = −0.359, p = 0.023; and r s = −0.371, p = 0.018; respectively). Significant positive correlation was found between FOUR score on the admission date and right and left mSSEP P15-N20 amplitude (r s = 0.595, p < 0.0001; and r s = 0.383, p = 0.015; respectively). Significant positive correlation was obtained between right and left mSSEP P15-N20 amplitude and discharge day GCS value (r s = 0.466, p = 0.002; and r s = 0.336, p = 0.034), as well as with FOUR score at the discharge day (r s = 0.340, p = 0.032; and r s = 0.319, p = 0.045). Significant negative correlation was established between right and left mSSEP P15-N20 amplitude and mRS at the day of discharge(r s = −0.497, p = 0.001; and r s = −0.381, p = 0.015). Conclusion: Results of evoked potentials, particularly mSSEP, demonstrated significant correlation with clinical outcomes. Results of our study indicate that mSSEP has potential value in prediction of clinical outcome in patients with hemorrhagic stroke.